2015
DOI: 10.1155/2015/924028
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Cytokines Production by Indomethacin Acute Dose during the Evolution of Ehrlich Ascites Tumor in Mice

Abstract: The aim of the present study was to investigate the influence of a nonselective COX1/COX2 inhibitor (indomethacin) on tumor growth of Ehrlich Ascites Tumor (EAT) in mice, using as parameters the tumor growth and cytokine profile. Mice were inoculated with EAT cells and treated with indomethacin. After 1, 3, 6, 10, and 13 days the animals were evaluated for the secretion of TNFα, IL-1α, IL-2, IL-4, IL-6, IL-10, and IL-13 and PGE2 level in peritoneal cavity. The results have shown that EAT induces PGE2 productio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 38 publications
(32 reference statements)
0
6
0
1
Order By: Relevance
“…Cumulatively the Indo group results indicate a severe gastric injury and delayed healing. One previous rat study showed that Indo induced the COX-2 expression [ 39 ]; simultaneously, another previous study revealed that Indo has been shown to induce the IL6/TNFα level and inhibited the PGE2 level [ 40 ]. While in normal gastric mucosa COX-1 is the predominant COX isoenzyme, there is increasing evidence that detectable amounts of COX-2 mRNA and protein are expressed both constitutively and inducible in gastric mucosa [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…Cumulatively the Indo group results indicate a severe gastric injury and delayed healing. One previous rat study showed that Indo induced the COX-2 expression [ 39 ]; simultaneously, another previous study revealed that Indo has been shown to induce the IL6/TNFα level and inhibited the PGE2 level [ 40 ]. While in normal gastric mucosa COX-1 is the predominant COX isoenzyme, there is increasing evidence that detectable amounts of COX-2 mRNA and protein are expressed both constitutively and inducible in gastric mucosa [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…The antiviral activity of indomethacin was shown to be associated with blocking viral replication [90] . However, another interesting pharmacological effect of indomethacin that could contribute to COVID-19 patient recovery is its capacity to modulate cytokine production [91] , [92] , particularly the robust effect this drug has on reducing the release of proinflammatory IL-6 [93] . The ability of indomethacin to attenuate inflammatory processes in combination with its antiviral properties make it a good candidate in the fight against the coronavirus.…”
Section: Drug Repurposing For Covid-19 and Affected Cytokinesmentioning
confidence: 99%
“…Tumor necrosis factor-alpha (TNF-α) is involved in tumor growth, angiogenesis and metastasis in EAC model 21 . In addition, interleukin (IL)-6 and prostaglandin E2 (PGE2) expressions were elevated in EAC and human ascetic tumors 22 , 23 . Inflammatory PGE2 expression is the result of overactivation of arachidonic acid pathway through the action of phospholipase A2 enzyme.…”
Section: Introductionmentioning
confidence: 99%